2018
DOI: 10.1002/jlcr.3584
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological properties of radiohalogenated α,α‐disubstituted amino acids for PET and SPECT imaging of amino acid transporters (AATs)

Abstract: Fluorine-18 and iodine-123 labeled nonnatural alicyclic and methyl branched disubstituted α,α-amino acids are a diverse and useful class of tumor imaging agents suitable for positron emission tomography and single photon emission computed tomography. These tracers target the increased expression of the cell membrane amino acid transporter systems L, ASC, and A exhibited by many human tumor cells. The most established clinical use for these radiolabeled amino acids is imaging primary and recurrent gliomas and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…Thin-layer chromatography was performed on Merck silica gel plates and visualized by UV light and/or potassium permanganate. 1 H NMR and 13 C and 19 F NMR spectra were recorded on Bruker 600, Varian INOVA 600, INOVA 500, and INOVA 400 spectrometers. Residual solvent resonances were treated as internal reference signals.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thin-layer chromatography was performed on Merck silica gel plates and visualized by UV light and/or potassium permanganate. 1 H NMR and 13 C and 19 F NMR spectra were recorded on Bruker 600, Varian INOVA 600, INOVA 500, and INOVA 400 spectrometers. Residual solvent resonances were treated as internal reference signals.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Residual solvent resonances were treated as internal reference signals. 19 F spectra were referenced to either trifluoroacetic acid (−76.55 ppm) or fluorobenzene (−113.15 ppm). IR spectra were recorded on a Nicolet iS10 FT-IR spectrometer, and the absorption peaks were reported in cm −1 .…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, non-natural AAs offer a platform for the incorporation of 18 F, a radionuclide with a more than fivefold longer half-life and a shorter positron range than 11 C. Moreover, certain non-natural AA scaffolds have been demonstrated to confer metabolic stability while maintaining avidity for transport by AATs. Several decades ago, Washburn and coworkers reported that 14 C labeled 1-aminocyclobutane carboxylic acid (ACBC) and 1-aminocyclopentane carboxylic acid (ACPC) have high tumor avidity and good in vivo stability. Following these reports, Goodman and coworkers prepared and biologically evaluated several 18 F radiolabeled analogues of ACBC . Their biological transport was assessed in 9L gliosarcoma cells and, in each case, was mediated primarily by system ASC, though some transport by system L was observed.…”
mentioning
confidence: 99%
“…16−19 Following these reports, Goodman and coworkers prepared and biologically evaluated several 18 F radiolabeled analogues of ACBC. 20 Their biological transport was assessed in 9L gliosarcoma cells and, in each case, was mediated primarily by system ASC, though some transport by system L was observed. In Fischer rats bearing 9L gliosarcoma, [ 18 F]FACBC derivatives demonstrated good brain uptake and much higher tumor to contralateral brain tissue ratios than [ 18 F]FDG.…”
mentioning
confidence: 99%